The Accuracy of Al and Cu Film Thickness Determinations and the Implications for Electron Probe Microanalysis. (27th April 2018) - Matthews, Mike B.; Kearns, Stuart L.; Buse, Ben
Abstract: The accuracy to which Cu and Al coatings can be determined, and the effect this has on the quantification of the substrate, is investigated. Cu and Al coatings of nominally 5, 10, 15, and 20 nm were sputter coated onto polished Bi using two configurations of coater: One with the film thickness monitor (FTM) sensor colocated with the samples, and one where the sensor is located to one side. The FTM thicknesses are compared against those calculated from measured Cu L α and Al K α k -ratios using PENEPMA, GMRFilm, and DTSA-II. Selected samples were also cross-sectioned using focused ion beam. Both systems produced repeatable coatings, the thickest coating being approximately four times the thinnest coating. The side-located FTM sensor indicated thicknesses less than half those of the software modeled results, propagating on to 70% errors in substrate quantification at 5 kV. The colocated FTM sensor produced errors in film thickness and substrate quantification of 10–20%. Over the range of film thicknesses and accelerating voltages modeled both the substrate and coating k -ratios can be approximated by linear trends as functions of film thickness. The Al films were found to have a reduced density of ~2 g/cm 2 .